(untitled) (Texas Journal of Engineering and Technology, 2023)
Manado City is one of the second largest cities on the northern island of Sulawesi with a population growth rate that continues to increase from year to year, in 2013 the population reached 419,596 people, and in 2020 the population reached 451.616 people, in 2020 the waste produced was 121.504,81 tons / year with a population of 451,616, and in 2021 the waste produced is 124,059.81 Tons / Year with a population of 453.182, the amount of waste that can be managed by the Manado City Government is 107.408 Tons / Year (86.58%), for details of waste managed is 17.618 Tons / Year (14.20%) waste processed at the Sumompo Landfill is 89.790 Tons / Year (72.38%), of the amount of waste produced is not supported by adequate waste processing facilities, in Manado City waste processing facilities such as TPS 3R = 2 units, waste banks = 3 units, compost houses = 0 units, Incinerators = 4 units. Based on this background, waste processing facilities are examined in order to analyze the costs and benefits of developing waste treatment facilities in Manado City. using three variables to obtain the highest Net Value and BCR values, for Net Value and BCR values from the first alternative Net Value of Rp. 9.657.293.149,41 with a BCR value of 6.90, for the second alternative Net Value -Rp 480.866.953,75,- with a Benefit Cost Ratio value of "0.67", and for the third alternative Net Value of Rp. 235.498.801,75 with a Benefit Cost Ratio value of "1.30", The first alternative is alternative which is recommended to be applied because the BCR value > 1. From these results, it is expected to provide information to waste management authorities in Manado City in choosing alternative 3R TPS based on Net Value, Benefit Cost Ratio and Analyzes Sensitivity.